2010
DOI: 10.1007/s11630-010-0405-x
|View full text |Cite
|
Sign up to set email alerts
|

Improving film cooling performance by using one -inlet and double-outlet hole

Abstract: The film cooling performance of a trunk-branch hole is investigated by numerical simulation in this paper. The geometry of the hole is a novel cooling concept, which controls the vortices-pair existing at the trunk hole outlet using the injection of the branch hole. The trunk-branch holes require easily machinable round hole as compared to the shaped holes. The flow cases were considered at the blowing ratios of 0.5, 0.75, 1.0, 1.5 and 2.0. At the low blowing ratio of 0.5, the vortices-pair at the outlet of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Enhanced film cooling effectiveness was obtained by the new design compared to the base line case, the circular scheme. A similar design was proposed by Li and Zhang [12]. The scheme they proposed is a circular scheme with one inlet and double outlet, Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Enhanced film cooling effectiveness was obtained by the new design compared to the base line case, the circular scheme. A similar design was proposed by Li and Zhang [12]. The scheme they proposed is a circular scheme with one inlet and double outlet, Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Park et al [6] presented the control of vortex flows by using forward and backward injection jets with various vortex intensities and hole dispositions to increase FE. Li and Zhang [7] numerically analyzed the effect of the geometry of the hole on the FE of a hole under trunk-branch shape with various M. The results showed that the FE is improved at M = 0.5. Li et al [8] numerically investigated the effect of the aperture ratios and injection angles of sister-shaped holes on FE.…”
Section: Introductionmentioning
confidence: 99%
“…Generating vortex technique is primarily a flow control technique whose effect in mitigating the CRVP action depends on the generated vortex location and strength. In this technique, the common anti-vortex generators include the use of chevron as shown by Abdala and Elwekeel [5], one-inlet double-outlet hole as presented by Li and Zhang [6], backward injection holes as presented by Park et al [7], or ramp upstream of the injection holes as presented by Na and Shih. [8] and Zhou and Hu.…”
Section: Introductionmentioning
confidence: 99%